Influence of surgery involving tendons around the knee joint on ankle motion during gait in patients with cerebral palsy - Lee, Seung Yeol; Kwon, Soon Sun; Chung, Chin Youb; Lee, Kyoung Min; Sung, Ki Hyuk; Kim, Sangwoo; Park, Moon Seok (BMC Musculoskeletal Disorders, 2018)
Background: Simultaneous motion of the knee and ankle joints is required for many activities including gait. We aimed to evaluate the influence of surgery involving tendons around the knee on ankle motion during gait in the sagittal plane in cerebral palsy patients. Methods: We included data from 55 limbs in 34 patients with spastic cerebral palsy. Patients were followed up after undergoing only distal hamstring lengthening with or without additional rectus femoris transfer. The patients' mean age at the time of knee surgery was 11.2 ± 4.7 years, and the mean follow-up duration was 2.2 ± 1.5 years (range, 0.9-6.0 years). Pre- and postoperative kinematic variables that were extracted from three-dimensional gait analyses were then compared to assess changes in ankle motion after knee surgery. Outcome measures included ankle dorsiflexion at initial contact, peak ankle dorsiflexion during stance, peak ankle dorsiflexion during swing, and dynamic range of motion of the ankle. Various sagittal plane knee kinematics were also measured and used to predict ankle kinematics. A linear mixed model was constructed to estimate changes in ankle motion after adjusting for multiple factors. Results: Improvement in total range of motion of the knee resulted in improved motion of the ankle joint. We estimated that after knee surgery, ankle dorsiflexion at initial contact, peak ankle dorsiflexion during stance, peak ankle dorsiflexion during swing, and dynamic range of motion of the ankle decreased, respectively, by 0.4° (p = 0.016), 0.6° (p < 0.001), 0.2° (p = 0.038), and 0.5° (p = 0.006) per degree increase in total range of motion of the knee after either knee surgery. Furthermore, dynamic range of motion of the ankle increased by 0.4° per degree increase in postoperative peak knee flexion during swing. Conclusions: Improvement in total knee range of motion was found to be correlated with improvement in ankle kinematics after surgery involving tendons around the knee. As motion of the knee and ankle joints is cross-linked, surgeons should be aware of potential changes in the ankle joint after knee surgery.
Keywords: Adolescent; Ankle Joint; Cerebral Palsy; Child; Female; Follow-Up Studies; Gait; Humans; Knee Joint; Male; Orthopedic Procedures; Range of Motion, Articular; Retrospective Studies; Tendons; Ankle kinematics; Cerebral palsy; Distal hamstring lengthening; Gait analysis; Rectus femoris transfer